KEDAH TUA FESTIVAL 2016: REVEALING SOUTH-EAST ASIA’S UNIQUE EARLY CIVILISATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 17 May 2016 Universiti Sains Malaysia (USM) through its Centre for Global Archaeological Research (PPAG) and the National Heritage Department (JWN), together with the Kedah State Government, Northern Corridor Implementation Authority (NCIA), Malaysian Inbound Tourism Association (MITA) and the Malaysian Institute of Architects (MIA) would be organising the Kedah Tua Festival (FKT) to promote the unique attractions of Sungai Batu as the oldest civilisation site in SouthEast Asia.